Search on partially ordered structures - Skobelev , V. G.; Скобелев , В. Г. (Institute of Mathematics, NAS of Ukraine, 1992)
General methods are developed to search for minimal and dead-end payoff operators for a class of sources endowed with a partial order structure. It is shown that the results can be used in the design of experiments with automata and in the minimization of Boolean functions.